2022
DOI: 10.3390/soilsystems6040093
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Soil Properties Affected by Invasive Plants in Southwest Germany (Rhineland-Palatinate)—A Case Study

Abstract: The invasive plant species Impatiens glandulifera native to Asia mainly occupies European riparian ecosystems. It is still unclear to which extent this invasive plant can alter physico-chemical soil properties in terms of carbon turnover, microstructural stability and soil hydraulic properties threatening native plant species, here represented by Urtica dioica. Soil samples were collected from three sites in the Palatine forest near the river Queich, including bare soil (Control), or soil within dense stands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…The two-way ANOVA demonstrated a significant effect (P < 0.05 or 0.01) of plant species, depths and their interaction on all soil chemical properties under study, with the exception of Ec, HCO 3 and SO 4 -by depth factor, as well as pH, Ec and Ca ++ by species x depths interaction. Our results were in line with El-Absy [6], El-Absy and Kamel [13], Han et al [52] and Jamin et al [53].…”
Section: Soil Analysissupporting
confidence: 91%
“…The two-way ANOVA demonstrated a significant effect (P < 0.05 or 0.01) of plant species, depths and their interaction on all soil chemical properties under study, with the exception of Ec, HCO 3 and SO 4 -by depth factor, as well as pH, Ec and Ca ++ by species x depths interaction. Our results were in line with El-Absy [6], El-Absy and Kamel [13], Han et al [52] and Jamin et al [53].…”
Section: Soil Analysissupporting
confidence: 91%
“…Invasive plant species can outcompete and reduce the abundance of native plant species [ 42 ], alter soil properties [ 26 ], and homogenize the biodiversity of invaded communities and ecosystems [ 43 ]. Invasive plant species may alter soil properties in their new ranges, but the magnitude and direction of these changes are sometimes unique to each invasive species and often vary among habitats for the same non-native species [ 6 , 8 , 12 , 32 , 33 , 44 , 45 ]. To the best of our knowledge, this is the first study to investigate the biogeochemical consequences of the invasion of Prosopis juliflora , Ipomoea carnea , Leucaena leucocephala , and Opuntia ficus-indica in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported no statistically significant difference among the properties and microelements of soils from habitats infested with invasive plant species compared to the soils of equivalent habitats occupied by native plant species [ 6 , 8 , 12 , 32 , 33 ]. Moreover, several studies that have compared the capacity of multiple invasive species to alter soil properties within the same experiments design have revealed contrasting results among the species examined [ 6 , 8 , 32 ].…”
Section: Introductionmentioning
confidence: 94%
“…Although I. glandulifera is defined as a transformer species [ 58 ], conclusions about its impact on species composition, diversity, and richness vary from “insignificant” [ 59 , 60 , 61 ] to “prominent” [ 62 , 63 , 64 , 65 , 66 ]. However, the differences can be attributed to factors such as the initial conditions of the invasion sites [ 67 ], the residence time in the invasion site [ 68 ], and local species composition [ 62 ].…”
Section: Introductionmentioning
confidence: 99%